PENGARUH TUNTUTAN PEKERJAAN, KEPUASAN KERJA, DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KETERLIBATAN KERJA (Studi pada Karyawan SPBU Simongan dan SPBU Indraprasta Semarang) - Rahmadianti, Raissa Faristia; Lataruva, Eisha (Diponegoro Journal of Management, 2023)
ABSTRACT Human resources with good capabilities are not enough to face business competition in this modern era. Companies need employees who engage to them so that they will give maximum effort every time they do works. Every company has its own job demands that must be carried out by its employees. Job demand then affect the condition and welfare of employees. Furthermore, every company have to pay more attention to employee’s job satisfaction and perceived organizational support because they are related to work engagement. The purpose of this study is to find out the effect of job demand, job satisfaction, and perceived organizational support towards work engagement among the employees of SPBU Simongan and SPBU Indraprasta Semarang. Population in this study were employees of SPBU Simongan and SPBU Indraprasta Semarang. This research was conducted by distributing questionnaires to 60 samples of employees using a saturated sampling method. The distribution of questionnaires in this study was distributed personally administered questionnaires. The data analysis method is using Multiple Linear Regression using SPSS 27.0 The results of the study on employee of SPBU Simongan and SPBU Indraprasta show that job demand has a negative and significant effect on work engagement. Meanwhile, job satisfaction has a positive and significant effect on work engagement. Last, perceived organizational support also has a positive and significant effect on work engagement.